Riesgo obstétrico materno asociado a parto pretérmino, en gestantes entre 15 a 40 años, Hospital Martín Icaza, Babahoyo, Los Ríos, enero - junio 2019. - Carranza Macias, Narcisa Maria (2020)
Determining maternal obstetric risk factors associated with pre-term birth is vital importance in Ecuador, where pre-maturity is related to around a third of all neonatal deaths, who gets to survive will suffer disability during all their lives corresponding to 45% of infants with infantile cerebral palsy, 35% of infants with visual problems and 25% with cognitive disabilities, becoming a real National problema. The current job retrospective-quantitative research was carried out with the purpose of determining the maternal obstetric rick factors associated with pre-term birth in prenant women treated in the gynecology-obstetrics emergency area of the General Martín Icaza Hospital, in Babahoyo, city, Los Ríos provivince- Ecuador from January to June 2019. The analysis of the statistical data showed that the population with the highest incidence of pre-term birth is the urban area with 67%, with a higher percentage prevailing in those pregnant women who presented low obstetric rick, for that reason, the theoretical proposal seeks to reinforce Community intervention programs compiled in different strategies proposed by the Ministry of Public Health whose purpose is tha pregnant women know how to recognize the main factors of maternal obstetric rick to prevente this sydrome as much as possible, promoting, attending continuous pre-natal controls to reduce the neonatal and maternal morbid mortality.